The quantification of the extent of flooding on selected major Afrotropical lakes to guide management implications - Aura, Christopher Mulanda; Nyamweya, Chrisphine; Musa, Safina; Ogari, Zachary; Owoko, Winnie; Osore, Melckzedeck; May, Linda; Njiru, James M. (Frontiers in Environmental Science, 2023)
The extent of flooding in vulnerable inland and lacustrine systems can demonstrate the coverage and the magnitude of such phenomenon for policy enhancement. This study examined the extent of flooding due to rising water levels in selected Afrotropical lakes to guide interventions that would sustain the livelihoods of communities affected. The years that were most prone to flooding (2010 and 2020) were used as a baseline in the extraction of changes in spatial extent and area of lacustrine shoreline, and rainfall and satellite altimetry data, using geospatial and remote sensing technologies. The extent of flooding was strongly but insignificantly related (R2 = 0.63; p = 0.07) to the sizes of the studied lakes and the amount of rainfall. Lakes with the smallest surface areas such as Baringo and Naivasha showed the greatest increase in flooding of 52.63% and 42.62%, respectively. Larger lakes such as Lakes Victoria (1.05%), Turkana (3.77%), and Tanganyika (0.07%) had the lowest increases in areal extent. Furthermore, the topography of the lakes studied further determined the residence time and the extent of flooding, such that lakes such as Edward (-0.09%) and Rukwa (-3.25%) receded during the period when other lakes were flooding. The information and data presented here provides the most up-to-date quantification of flooding to support adaptation strategies for inland lake systems and guide policy implementation.